EVALUASI PROGRAM DESA MAJU INHIL JAYA PLUS TERINTEGRASI MELALUI BADAN USAHA MILIK DESA DANAU PULAI INDAH KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR TAHUN 2019-2020 - Sesih Sugesti; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The existence of the Desa Maju Inhil Jaya Plus Integrated Program with the sub program 1 Village 1 BUM Desa shows that every village in Indragiri Hilir Regency is required to have a BUM Desa. The phenomenon is that the society has difficulty in finding and developing the potential of the village, the lack of commitment of the parties who cooperate in the implementation of BUM Desa, and difficulties in marketing products that have been produced by the village community. This study uses the evaluation theory proposed by William N Dunn. Evaluation is concerned with the production of information about the benefits from the results of a policy or program outcome. The indicators are effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. Which method used in this research is qualitative. The type of research is descriptive qualitative research. The research location is in Indragiri Hilir Regency and Danau Pulai Indah Village. The results showed that the Desa Maju Inhil Jaya Plus Integrated Program is the Regent's flagship program for the 2018-2023 period with the focus is on improving the rural economy through BUM Desa as the axis. Desa Maju Inhil Jaya Plus Integrated Program has not yet been able to achieve the goals. This program can be said to be right with the aim of boosting the rural economy through BUM Desa. However, it still has obstacles such as human resources who are less willing to move, BUM Desa managers who are less active and even inactive and marketing of derivative products are still limited. Keywords: Effectiveness and Efficiency, Adequacy and Equity, Responsiveness and Accuracy